2022
DOI: 10.3389/fpsyt.2022.998807
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dysfunction and cortical structural abnormalities in first-episode drug-naïve schizophrenia patients with auditory verbal hallucination

Abstract: ObjectiveThe current study aimed to examine the cognitive profiles and cortical structural alterations in first-episode drug-naïve schizophrenia with AVH (auditory verbal hallucination).MethodsCortical structural parameters including cortical thickness and local gyrification index (LGI) estimated using FreeSurfer as well as cognitive performance assessed on the MATRICS Consensus Cognitive Battery (MCCB) were acquired from 78 schizophrenia patients with AVH, 74 schizophrenia patients without AVH (non-AVH), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Specifically, our study found a large effect size for impaired working memory and attentional vigilance in UMFE patients compared to healthy controls. Interestingly, no deficits in social cognition were observed in this group, which contradicts the findings of most earlier studies ( 34 , 36 , 37 ). For example, Pablo et al ( 38 ) reported that both first-episode and chronic schizophrenia were associated with social cognition deficits.…”
Section: Discussionsupporting
confidence: 53%
“…Specifically, our study found a large effect size for impaired working memory and attentional vigilance in UMFE patients compared to healthy controls. Interestingly, no deficits in social cognition were observed in this group, which contradicts the findings of most earlier studies ( 34 , 36 , 37 ). For example, Pablo et al ( 38 ) reported that both first-episode and chronic schizophrenia were associated with social cognition deficits.…”
Section: Discussionsupporting
confidence: 53%
“…Among these, we pay particular attention to the superior parietal gyrus in conjunction with the thalamus because of its implication in several cognitive domains in association with the role of the prefrontal cortex among patients with schizophrenia. [44][45][46]…”
Section: Discussionmentioning
confidence: 99%
“…We thought that the ventral (pregenual) ACC was a better region to focus on compared to the dorsal ACC to test our hypotheses. This was because both being bullied and having psychotic experiences, especially the former, are related to emotional dysregulation [ 22 , 70 ], and because several previous neuroimaging studies reported the roles of the ventral ACC both in psychosis [ 71 73 ] and in emotional social stress [ 74 76 ]. Thus, in this study, we explored the association of pregenual ACC glutamate levels with subclinical psychotic experiences over time using a two-time-point longitudinal dataset with more than 200 adolescents recruited from the Tokyo TEEN Cohort (TTC) study [ 77 , 78 ].…”
Section: Introductionmentioning
confidence: 99%